Entrepreneurial Choices of Initial Human Capital Endowments and New Venture Success - Vera Rocha; Mirjam C. van Praag; Timothy B. Folta; Anabela Carneiro (Institute for the Study of Labor (IZA), 2016)
The founder (team)'s human capital is a vital determinant of future firm performance. This is a stylized fact. Less is known about the effect of the human capital of the initial workforce hired by the founder(s). We study the performance consequences of a founder's choice of the initial workforce's human capital (quantity and quality), besides the human capital of the founder(s). The analysis is based on matched employer-employee data and covers about 5,300 startups in manufacturing industries founded by individuals coming from employment between 1992 and 2007. We acknowledge that initial hiring decisions are endogenous and correlated with the human capital of the founders and the ownership structure of startups (single founder versus team of founders). Given the stickiness of initial choices, human capital decisions at entry turn out to be a close to irreversible matter with significant implications for post-entry survival and growth of the firm.
Keywords: J24; J25; L26; M13; 330; human capital; entrepreneurship; startups; firm performance